Association between polymorphisms in pre-miRNA genes and risk of oral squamous cell cancer in a Chinese population. - Enjiao Zhang; Zhongfei Xu; Weiyi Duan; Shaohui Huang; Li Lu (PLoS ONE)
Background MicroRNAs play important roles in the development of human cancers. This case-control study is to evaluate the roles of the polymorphisms in pre-miRNAs on risk of oral cancer in a Chinese population. Methods The genotypes of three polymorphisms were determined in 340 patients with oral squamous cell cancer and 340 healthy controls who were frequency matched for age and sex. Odds ratios (ORs) and 95% confidence intervals (95%CIs) were calculated to assess the association. All analyses were performed using the SPSS software. 3.154() 0.001. Results For miR-499 rs3746444, individuals carrying homozygous CC genotype had increased risks of oral cancer compared with the homozygous wild TT genotype (adjusted OR was 3.154, 95%CI was 1.555-6.397, P value was 0.001). The C allele of miR-499 rs3746444 was associated with a higher risk of oral cancer with significant odds ratio of 1.453. In the stratified analyses by sex, the associations between miR-499 rs3746444 and miR-146a rs2910164 polymorphisms with the susceptibility of oral squamous cell cancer were significant in males. However, with 1/4 as many subjects there were no significant associations between the three polymorphisms and oral cancer risks in females. The joint effects of miRNA polymorphisms and smoking on the risk of OSCC were analyzed and the results suggested that the association between microRNA genetic variants and OSCC risk was modified by smoking. Conclusions These findings suggest that miR-499 rs3746444 and miR-146a rs2910164 polymorphisms may contribute to genetic susceptibility to oral squamous cell cancer.